2006
DOI: 10.1080/10401230600801234
|View full text |Cite
|
Sign up to set email alerts
|

Do Certain Atypical Antipsychotics Increase the Risk of Diabetes? A Critical Review of 17 Pharmacoepidemiologic Studies

Abstract: The preponderance of current epidemiologic evidence indicates that olanzapine therapy poses a higher risk of diabetes than untreated major psychiatric illness, and that olanzapine confers greater risk of diabetes than risperidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 68 publications
5
40
0
1
Order By: Relevance
“…The finding that the current use of the SGAs, olanzapine, and clozapine increases the risk of diabetes is consistent with earlier findings (Gianfrancesco et al, 2002;Ramaswamy et al, 2006;Smith et al, 2008;Stahl et al, 2009;Yood et al, 2009). However, to our knowledge, this is the first study showing that the metabolic effects of olanzapine early or during treatment can alter the trajectory to diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that the current use of the SGAs, olanzapine, and clozapine increases the risk of diabetes is consistent with earlier findings (Gianfrancesco et al, 2002;Ramaswamy et al, 2006;Smith et al, 2008;Stahl et al, 2009;Yood et al, 2009). However, to our knowledge, this is the first study showing that the metabolic effects of olanzapine early or during treatment can alter the trajectory to diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…In the first half of the last century, female sex was considered as risk factor for type 2 diabetes, but this difference had vanished by the end of the last century (Gale and Gillespie, 2001). However, in a review of pharmacoepidemiologic studies of antipsychotic use and diabetes, an association with female sex was also found similarly in our study (Ramaswamy et al, 2006). Future studies should investigate sex differences regarding the antipsychotic effects and lifestyle influences that could affect diabetes risk in antipsychotic-treated individuals.…”
Section: Discussionsupporting
confidence: 54%
“…The lower risk of tardive dyskinesia may be one area in which second-generation antipsychotics have an advantage of first-generation antipsychotics, although this is recently been questioned (35) and may be overshadowed by the greater risk of diabetes, obesity, and other related conditions (4); many of these risks were disclosed during our study period (38). Secondgeneration antipsychotics will only increase in use as they begin to come off patent, opening the market for less expensive generic substitutes, and triggering a wave of less restrictive policies, especially in Medicaid and Medicare Part D formularies.…”
Section: Discussionmentioning
confidence: 91%
“…Autoimmune pathogeneses of schizophrenia have been hypothesized and the clinical delineation of a potentially corresponding subset of patients has been addressed in young female patients who carry the concomitant diagnoses of schizophrenia, brittle type 1 diabetes, and hypothyroidism. These patients when treated with corresponding antipsychotic medication on an acute basis, an apparent resolution of their brittle type 1 diabetes with the successful treatment of their psychotic disorder is observed (Balter et al, 2004;Ramaswamy et al, 2006). This well documented link between antipsychotic agents and changes in blood glucose may be of benefit in a subset of patients who suffer from both psychotic and diabetic disorders.…”
Section: Aetiology and Pathophysiologic Substrate: From The Suspicionmentioning
confidence: 99%